Co-Witness Auditory Memory Conformity following Discussion: A Misinformation Paradigm. Issue 2 (April 2014) - Mori, Kazuo; Kishikawa, Takeshi
Twenty-four Japanese undergraduate pairs (12 male and 12 female pairs) participated as witnesses to a simulated criminal event. Although the witness pairs watched the same video together, through wireless headphones they experienced two different auditory versions with four differing items without being aware of the discrepancies. After the presentation, the witnesses were led to discuss six items, including two critical ones they had heard differently and another four they had heard in common. Witness memory performance was assessed individually with multiple-choice questionnaires in three sessions: before the discussion, after the discussion, and 1 week later. The results showed that participants tended to conform to their co-witness more often on the discussed items than on the not-discussed items. Source monitoring analyses on the four critical items revealed that even those participants who conformed were mostly cognizant of the source of their information just after the discussion, but they were prone to source-monitoring errors a week later.